“Proposal of a management model for improving municipal address of the province of Otuzco” - Ramos Gonzales, Heriberto Werenshon (2012)
The following article is a study of the government’s structure and management of Otuzco Municipal’s committee. This paper focuses on historical and sociological government function analyses, both executively and technically, with a purpose of purposing implementable improvements to the city’s management of infrastructure and public service. The results from a survey collected between 2007 and 2010 showed areas of incompetence and limitations in the government’s administration, use of resources and public service delivery. There is a need to implement public administration changes in order to increase the city’s efficiency, improve standard of life for its citizens and further local development in certain key areas. After a comparative analysis, we propose the “Management Model EFQM.Therefore, the proposed “EFQM Management Model” provides suggestions to improve government leadership and structure effectively use resources and develop a realistic approach to reduce poverty and guarantee sustainable city development.